New nomenclature combinations for vascular plant taxa (CHORNOMORSKI BOTANICAL JOURNAL, 2010)
Some new nomenclature combinations in Achillea L., Buglossoides Moench, Lotus L., Pseudolisymachion Opiz, Pulsatilla Mill. та Ranunculus L. are proposed.
Keywords: nomenclature combinations, vascular plants, northern Black Sea Coast.